Pesantren-Based Character Education in Counteracting Juvenile Delinquency: A Case Study at Fadllillah Islamic Boarding School - Nuruzzaman, Muhammad Adib; Darussalam, Afghan Fadzillah; Aisyah, Aisyah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This study aims to investigate the implementation of pesantren-based character education in addressing juvenile delinquency, through a case study at Pondok Pesantren Fadllillah Tambak Sumur Sidoarjo. Employing qualitative methods and a case study design, the research delves into understanding how character education in pesantren contributes to combating juvenile delinquency. Data were collected through document analysis, observation, and in-depth interviews with pesantren administrators, teachers, and students. The results indicate that character education at Pondok Pesantren Fadllillah makes a positive contribution through fostering religious values, social projects, and leadership training. The character education approach, centered on Islamic teachings and noble ethics, along with intensive guidance from kyai (spiritual leaders) and pesantren administrators, has a positive impact on adolescent behavior. This research provides crucial insights for educational institutions and communities, supporting an understanding of the potential of pesantren-based character education in addressing juvenile delinquency and cultivating a high-quality younger generation. It is hoped that the findings contribute to the development of more effective character education methods in various educational institutions.